Menumbuhkan Sikap Sosial Emosional EMC2 Terhadap Psychological Well-Being pada Siswa Sekolah Dasar - Nur Faizah; Irmawati Liliana (Scholaria: Jurnal Pendidikan dan Kebudayaan)
This research aims to foster social emotional attitudes EMC2 (Emphaty, Mindfulness, Compassion, Critical Inquiry) and photograph the process of implementing approaches to psychological well-being in English language learning. By implementing EMC2, it is hoped that students can develop social and emotional skills that have a positive impact on their psychological well-being. The observation method was used to monitor students' social interactions and emotional responses during learning, while interviews were conducted to gain an in-depth view of students' experiences and perceptions of learning English using the EMC2 approach. The results showed that the EMC2 approach significantly improved students' social emotional attitudes and psychological well-being. Students show (1) increased self-confidence. (2) social interaction skills. (3) emotional management. This research contributes to the development of knowledge in the field of education by offering a new approach that is effective in improving psychological well-being through learning English. These findings can be used as a reference for educators in designing holistic learning programs and supporting students' social emotional development.